Participation of ATMA (Agricultural Technology Management Agency) Members in Group Activities and Promotion of Sustainable Agricultural Practices in Karaikal District, Puducherry - Parthasarathi, Sundaram; Shaik Alauddin, A; Illakia, R; Hema, R (Journal of Extension Education, 2020)
A study was conducted in among five selected ATMA (Agricultural Technology Management Agency) groups. A total of 100 farmers from five groups were selected by employing random sampling. Participation was studied in three dimensions viz., group sustainability, sustainable agricultural practices and participation in post harvest technologies. The study reveals that majority of the members belong to medium level of participation in sustainable agricultural practices and participate more in group activities viz., group planning, maintaining transparency, decision making, shouldering responsibilities planning, decision making and auditing. Further, the study reveals that information source utilisation and information sharing behaviour of the group members showed a positive and significant relation with the participation of ATMA group members in sustainable agricultural practices. Addition of new members and lack in guidance were the problems expressed by the respondents. Group promoting initiatives and training on sustainable function of groups were the suggestions offered by the members of the group.